Adolescent Male and Female Gang Members’ Experiences with Violent Victimization, Dating Violence, and Sexual Assault - Gover, Angela R. (American journal of criminal justice, 2009)
A substantial amount of scholarship has been devoted to examining the relationship between gang membership and criminal offending. This research has produced a wealth of qualitative and quantitative studies indicating that gang membership increases the likelihood of criminal offending for both males and females. Less research, however, has examined the relationship between gang membership and violent victimization. The present study adds to the literature by examining the relationship between gender, gang membership, and three types of victimization. Specifically, this paper focuses on whether self-reported gang membership is uniquely related to victimization experiences for females compared to males. Results from a statewide survey of public high school students in South Carolina indicate that gang membership is significantly related to the risk of victimization for both males and females. The implications of these findings for research and policy are discussed.